Incident reporting and a culture of safety. (September 2016) - Hazan, Jonathan
Incident reporting has long been established as a key component of patient safety in almost all healthcare and related settings. The analysis of incidents to determine why they happen and put in place corrective actions enables us to learn from things that go wrong and protect patients from harm in the future. The introduction of electronic incident reporting using web forms to replace paper has improved efficiency and increased the number of reports collected. There still remain significant barriers to learning from incidents, however. These include issues to do with the design of the systems as well as issues concerning organisational culture. This article revisits the background and purpose of incident reporting in healthcare, discusses some of the barriers to effective reporting and suggests some approaches that can increase its usefulness in protecting patients from harm.